Digital literacy as a basis for a dialogue between the authorities and the population in the context of a pandemic - N. V. Prokazina (Цифровая социология)
In the conditions of self-isolation due to the COVID-19 pandemic and a significant reduction in the number of physical contacts, interaction in an online format through numerous social networks and platforms has become the main communication tool for citizens. It is they who provide the conditions for solidarity, dialogue and partnership. A serious change has affected the sphere of interaction between the population and the authorities: information and communication technologies, due to an increase in the number of citizens with a basic and primary level of education, have become the main help in the processes of building a dialogue between the authorities and the population.The purpose of this study is to analyse digital literacy, which is a key indicator that allows you to adequately assess the situation of interaction between the authorities and the population in the context of a pandemic and determine the directions for the development of dialogue. The main effects of such interaction are: increased activity due to the accessibility and ease of contacting the authorities; increased involvement of citizens in solving urgent problems of the local community and specific territories; increased trust as a result of active conscious joint activity of the population and authorities. Digital literacy has largely helped to mitigate the consequences of the pandemic, and the associated circumstances of the new reality. Citizens have the opportunity to receive services, submit appeals, applications, complaints to various authorities and other authorities in electronic format. Tools that ensure the involvement of public participation in management processes in a digital environment (as infrastructure components) have been created and are actively developing, and the presence of a basic level of digital competence of citizens allows you to include a large part of the population in these processes. One of the urgent tasks today is the further development of digital literacy, including the expansion of social groups of the population (socio-demographic, professional) that have an increased level of it.